393 IMPACTS OF CHILD LIFE INTERVENTION ON PEDIATRIC PATIENT AND PARENTAL PRE- AND POST-PROCEDURAL ANXIETY LEVELS. (1st January 2006) - Ghebremicael, S.; Yang, F.; Bright, R.
Abstract : Background: Pediatric patients and their parents experience various levels of anxiety prior to the patient undergoing a medical procedure, such as surgery. That anxiety can carry on post-procedure and have impacts on patient recovery and the parents' ability to provide support to their child. The Child Life Program consists of specialists who are trained to help patients and families understand and manage stressful healthcare situations such as these. Objective: The objective of this study is to determine if the receipt of Child Life Services (CLS) significantly impacts pediatric patient or parental anxiety in the outpatient surgery or outpatient procedural settings. Methods: Anxiety levels were measured in 72 subjects between the ages of 6 and 16, and their parents, using a modified Moller-Murphy Symptom Management Assessment Tool II Survey. The survey was completed at three times during the patient stay: registration, pre-procedural and at discharge. Independent and paired t-tests and the Pearson correlation test were used to calculate relationships. Results: Findings indicated that the receipt of CLS significantly decreased patient and parental anxiety levels ( p < .01). The average decrease in anxiety for CLS patients from the time of registration to just prior to surgery was 3.72 and 2.45 for their parents; for the control patients there was an actual increase in anxiety from registration to just prior to surgery of 2.56 and an average increase of 2.44 for their parents. For patients under the age of twelve years old there was a significant difference between the control and experimental subjects' anxiety levels at time of discharge (p < .05), where patients receiving CLS had lower anxiety levels (CLS patients' average 4.3, control patients' average 6.71). An inverse correlation existed between the patients' number of previous hospitalizations and their anxiety levels at registration (r = -.233, n = 72), while the number of previous hospitalizations had no general impact on patients anxiety levels just prior to surgery (r = -.117, n = 38). Conclusion: Patients and parents receiving CLS experience lower anxiety levels during their outpatient hospital experience and at the time of discharge as compared to patients without access to CLS. In addition, previous hospitalizations had less of an impact on anxiety levels at the time just prior to surgery than did the receipt of CLS, suggesting that CLS are an effective method of managing patient and parental anxiety.